Types and distribution of cancer patients attending in a tertiary care hospital of Bangladesh - Sharmin, Tanjina; Nikhat, Nazifa; Rayna, Shahrin Emdad; Khalequzzaman, Md; Khan, Fahmida Afroz; Rahman, KM Thouhidur; Islam, Tariqul; Haque, Syed Emdadul; Ahsan, Habibul; Kamal, Mohammed; Islam, Syed Shariful (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Bangladesh, similar to other countries is experiencing an increased burden of cancer. Absence of a national cancer registry has created a gap in the information regarding the presentation of cancer statistics of the country. The objective of this study was to assess the types and distribution of the cancer patients attending a tertiary academic medical center hospital in Bangladesh. A cross-sectional study was conducted among all the confirmed cancer patients attending the in-patient and out-patient, and daycare facilities in Bangabandhu Sheikh Mujib Medical University in October, 2019. A validated questionnaire, recommended by International Agency for the Cancer Registry was used to collect data. Written informed consent was obtained from every respondent. This study had received its ethical clearance from Institutional Review Board of BSMMU. Among the 1656 respondents, 78.8% were adult and 25.2% were from paediatric age groups. Leading cancer for adult males were lung cancer (9.6%), leukaemia (9.4%) and lymphoma (9.0%); and breast cancer (28.1%), thyroid cancer (16.1%), and cervical cancer (12.2%) for females. Leukaemia was the most frequent cancer in the paediatric group for both males (71.5%) and females (66.5%). Establishing a hospital-based cancer registry with high quality data in an academic medical center setting is feasible and can set the stage for establishing nationwide hospital-based as well as establishing a popula- tion-based cancer registry in Bangladesh, which is necessary to identify and tackle the rising burden of cancer in this country. BSMMU J 2022; 15(1): 43-49